2017
DOI: 10.1097/brs.0000000000001892
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Adjuvant Pain Medication Use and Outcomes Following Pediatric Spinal Fusion

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The combined use of acetaminophen/NSAIDs for opioid-based postoperative analgesia is widely applied after orthopaedic surgery including spinal fusion. There have been some reports investigating the effect of acetaminophen/NSAIDs on postoperative analgesia, focusing on spinal fusion surgery for scoliosis [ 12 14 ]. They showed that acetaminophen/NSAIDs reduced postsurgical pain.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of acetaminophen/NSAIDs for opioid-based postoperative analgesia is widely applied after orthopaedic surgery including spinal fusion. There have been some reports investigating the effect of acetaminophen/NSAIDs on postoperative analgesia, focusing on spinal fusion surgery for scoliosis [ 12 14 ]. They showed that acetaminophen/NSAIDs reduced postsurgical pain.…”
Section: Discussionmentioning
confidence: 99%
“…33 A 2017 database study using ICD9 codes for scoliosis and PSF procedure involving 7349 subjects at 38 children's hospitals found that gabapentinoid use was significantly associated with decreased odds of prolonged IV opioid use (OR 0.63, 95% CI 0.53-0.75) and called for further trials. 34 A recent randomized controlled trial involving 50 patients aged 10-19 found that pre and postoperative administration of gabapentin as an adjuvant to multimodal narcotic and NSAID analgesia significantly decreased both opioid use and visual analog pain scales in the first two postoperative days and suggested that gabapentin be considered as a standard medication for perioperative pain control in this population. 35 Another randomized study found decreased initial pain scores but no change in opioid related side effects with adjuvant gabapentin use.…”
Section: Gabapentin/pregabalinmentioning
confidence: 99%
“…43 A chart review of 7349 patient records from 38 children's hospitals found that postoperative ketorolac use was associated with decreased likelihood of prolonged IV opioid exposure. 34 A prospective, randomized, double-blinded, placebo-controlled trial with 36 adolescents assessing analgesic effects of low-dose ketorolac in conjunction with PCA found that compared to PCA alone, the ketorolac group had significantly lower pain scores on POD 1 and 2 and tolerated activity better on POD 1 with no differences in incidence of pruritus, nausea, vomiting, or constipation and no difference in incidence of curve progression, hardware failure, or back pain in the 2 years following spinal fusion. 44…”
Section: Nsaids or Acetaminophen As Adjuvantsmentioning
confidence: 99%
“…Multimodal pain management has been found to improve the quality of analgesia and reduce medication-related side effects after posterior spinal fusion (PSF) for adolescent idiopathic scoliosis (AIS) [ 1 – 7 ]. Prior studies have shown that perioperative gabapentin, an effective drug for neuropathic pain, combined with intravenous patient-controlled analgesia (PCA) reduces initial postoperative pain scores, postoperative opioid use, and time to completing physical therapy goals compared to PCA alone after PSF for AIS [ 1 , 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%